Question
O3/02/25 Grade 10 Factorise \( \begin{array}{ll}\text { a } x^{2}-7 x+12 & \text { () } 40 x^{2}+6 x y-18 y^{2} \\ \text { (b) } 2 x^{2}+12 x+18 & \text { (c) } 24 x^{2}-2 x y-y^{2} \\ \text { (c) } x^{2}-9 x+20 & \text { (j) } 3 x^{2}+19 x+20 \\ \text { d) } 3 x^{2}-9 x+24 & \\ \text { (e) } 2 x^{2}+5 x+3 & \\ \text { (t) } 3 x^{2}+4 x-4 & \\ \text { (g) } 5 x^{3} y+25 x^{2} y-30 x y\end{array} \)
Ask by Bob Barker. in South Africa
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
Here are the factorized forms of the given expressions:
a) \(x^{2} - 7x + 12 = (x - 3)(x - 4)\)
b) \(40x^{2} + 6xy - 18y^{2} = 2(5x - 3y)(4x + 3y)\)
c) \(2x^{2} + 12x + 18 = 2(x + 3)^{2}\)
d) \(24x^{2} - 2xy - y^{2} = (6x + y)(4x - y)\)
e) \(x^{2} - 9x + 20 = (x - 4)(x - 5)\)
f) \(3x^{2} + 19x + 20 = (3x + 4)(x + 5)\)
g) \(3x^{2} - 9x + 24 = 3(x^{2} - 3x + 8)\)
h) \(2x^{2} + 5x + 3 = (2x + 3)(x + 1)\)
i) \(3x^{2} + 4x - 4 = (3x - 2)(x + 2)\)
j) \(5x^{3}y + 25x^{2}y - 30xy = 5xy(x + 6)(x - 1)\)
Solution
Sure, let's factorize each of the given expressions step by step.
---
### **a) \(x^{2} - 7x + 12\)**
**Factorization:**
\[
x^{2} - 7x + 12 = (x - 3)(x - 4)
\]
**Explanation:**
We look for two numbers that multiply to **12** and add up to **-7**. These numbers are **-3** and **-4**.
---
### **b) \(40x^{2} + 6xy - 18y^{2}\)**
**Factorization:**
\[
40x^{2} + 6xy - 18y^{2} = 2(5x - 3y)(4x + 3y)
\]
**Explanation:**
1. **Factor out the Greatest Common Factor (GCF):**
\(40x^{2} + 6xy - 18y^{2} = 2(20x^{2} + 3xy - 9y^{2})\)
2. **Factor the quadratic:**
\(20x^{2} + 3xy - 9y^{2} = (5x - 3y)(4x + 3y)\)
---
### **c) \(2x^{2} + 12x + 18\)**
**Factorization:**
\[
2x^{2} + 12x + 18 = 2(x + 3)^{2}
\]
**Explanation:**
1. **Factor out the GCF:**
\(2x^{2} + 12x + 18 = 2(x^{2} + 6x + 9)\)
2. **Recognize a perfect square trinomial:**
\(x^{2} + 6x + 9 = (x + 3)^{2}\)
---
### **d) \(24x^{2} - 2xy - y^{2}\)**
**Factorization:**
\[
24x^{2} - 2xy - y^{2} = (6x + y)(4x - y)
\]
**Explanation:**
We look for two binomials that multiply to give the original quadratic:
\[
(6x + y)(4x - y) = 24x^{2} - 2xy - y^{2}
\]
---
### **e) \(x^{2} - 9x + 20\)**
**Factorization:**
\[
x^{2} - 9x + 20 = (x - 4)(x - 5)
\]
**Explanation:**
We look for two numbers that multiply to **20** and add up to **-9**. These numbers are **-4** and **-5**.
---
### **f) \(3x^{2} + 19x + 20\)**
**Factorization:**
\[
3x^{2} + 19x + 20 = (3x + 4)(x + 5)
\]
**Explanation:**
We find two numbers that multiply to \(3 \times 20 = 60\) and add up to **19**. These numbers are **15** and **4**.
\[
3x^{2} + 19x + 20 = 3x^{2} + 15x + 4x + 20 = (3x + 4)(x + 5)
\]
---
### **g) \(3x^{2} - 9x + 24\)**
**Factorization:**
\[
3x^{2} - 9x + 24 = 3(x^{2} - 3x + 8)
\]
**Explanation:**
1. **Factor out the GCF:**
\(3x^{2} - 9x + 24 = 3(x^{2} - 3x + 8)\)
2. **Note:**
The quadratic \(x^{2} - 3x + 8\) does not factor neatly with integers, so we leave it as is.
---
### **h) \(2x^{2} + 5x + 3\)**
**Factorization:**
\[
2x^{2} + 5x + 3 = (2x + 3)(x + 1)
\]
**Explanation:**
We look for two numbers that multiply to \(2 \times 3 = 6\) and add up to **5**. These numbers are **3** and **2**.
\[
2x^{2} + 5x + 3 = (2x + 3)(x + 1)
\]
---
### **i) \(3x^{2} + 4x - 4\)**
**Factorization:**
\[
3x^{2} + 4x - 4 = (3x - 2)(x + 2)
\]
**Explanation:**
We look for two numbers that multiply to \(3 \times (-4) = -12\) and add up to **4**. These numbers are **6** and **-2**.
\[
3x^{2} + 4x - 4 = 3x^{2} + 6x - 2x - 4 = (3x - 2)(x + 2)
\]
---
### **j) \(5x^{3}y + 25x^{2}y - 30xy\)**
**Factorization:**
\[
5x^{3}y + 25x^{2}y - 30xy = 5xy(x + 6)(x - 1)
\]
**Explanation:**
1. **Factor out the GCF:**
\(5xy\)
2. **Factor the quadratic:**
\(x^{2} + 5x - 6 = (x + 6)(x - 1)\)
3. **Combine:**
\(5xy(x + 6)(x - 1)\)
---
These are the fully factorized forms of the given expressions. If you have any further questions or need additional explanations, feel free to ask!
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Bonus Knowledge
Let's break these down with a spark of fun! For the first one, \(ax^2 - 7x + 12\): To factor this quadratic, think of two numbers that add up to -7 and multiply to 12. Those numbers are -3 and -4! So it factors to \(a(x - 3)(x - 4)\). Now, let's tackle \(5x^3y + 25x^2y - 30xy\): Here, the common factor is \(5xy\). Pull that out, and you get \(5xy(x^2 + 5x - 6)\). Next, factor the binomial as \((x + 6)(x - 1)\). So altogether, it's \(5xy(x + 6)(x - 1)\). Factor fun never ends, right?